HUKUM TIDAK TUNGGAL: POTRET PLURALISME HUKUM DALAM PENGATURAN KAWASAN TEMPAT SUCI PURA ULUWATU DI BALI - I Putu Sastra Wibawa (DHARMASMRTI: Jurnal Ilmu Agama dan Kebudayaan, 2018)
The research is titled ‘Law is not single: portrait of legal pluralism in the setting of the holy place of Uluwatu Temple in Bali’. Political legal pluralism is a policy approach as a middle ground or intersection in solving the problem of construction difference of holy place of Uluwatu temple in Bali, both from state law in the form of regional regulation concerning spatial plan and area of Bali Province and customary law of Pecatu custom village. Political legal pluralism tries to be an alternative way to unify the elements of state law, ethics / moral / religion, and society in order to achieve the sense of justice of Indigenous Peoples of Pecatu that owns the land that is exposed to the radius of the holy place of Uluwatu Temple. Political legal pluralism is an offer of legal policy based on the values of Pancasila philosophy. The theory used as a knife of analysis is the legal theory of law, as well as the theory of legal pluralism. This research is a qualitative research type, with socio-legal research approach with constructivism paradigm of law and using approach method of legal pluralism. Data source namely primary and secondary data collected by doing elaboration of field study and literature study that in narration with interpretive descriptive data processing.